Suture versus tacker closure of the peritoneum in transabdominal preperitoneal repair of inguinal hernia: A prospective comparative cohort study - C. Rajagopal; M. Sunil Krishna; Pavan M. Bhat (International Journal of Abdominal Wall and Hernia Surgery)
BACKGROUND: Laparoscopic transabdominal preperitoneal repair of inguinal hernia (TAPP) is routinely done by general surgeons. (1) One crucial step is peritoneal closure post-mesh placement to prevent contact with the bowel. (2) There are various techniques available for peritoneal closure. (3) This prospective comparative cohort study compares the effectiveness of sutures versus tackers in terms of time efficiency, cost, postoperative patient comfort, and complications. MATERIALS AND METHODS: This prospective comparative cohort study included patients undergoing unilateral TAPP at a tertiary care hospital in South India from December 2022 to April 2024. A total of 80 patients were included in the study, of which 50 underwent peritoneal closure by tackers and 30 underwent peritoneal closure by sutures based on the standard of care of the operating surgeon. These patients were observed intra-operatively, post-operatively, and during the first follow-up visit at 10–14 days and at 3 months. RESULTS: Peritoneal closure time was significantly lower for the tacker group (2.78 min vs. 11.17 min, P < 0.001). The tacker group had a higher cost (₹5313 vs. ₹1855, P < 0.001) and experienced increased postoperative pain at both 10–14 days (36% vs. 10%, P = 0.011) and 3 months (24% vs. 6.7%, P = 0.048). CONCLUSION: This study shows that although suturing for peritoneal closure is more time-consuming and technically challenging, it can significantly reduce the material cost and reduce both early and late postoperative pain. Using barbed suture materials can help reduce operative times. TRIAL REGISTRATION: Study registered under the Clinical Trial Registry of India. CTRI Number: CTRI/2022/11/047211.